Administrative coordination between the Federal Ministry and the local government and its impact on municipal performance An applied study in the municipalities of Dhi Qar Governorate - Mutar, Ammar Mahmood; Said, Abdul Salam Lefta (Journal of Economics and Administrative Sciences, 2021)
The aim of the research is to show the extent of the impact of administrative coordination on municipal performance after the state’s tendency to implement administrative decentralization and transfer of powers (administrative, legal, financial, and technical) from the Federal Ministry (construction, housing, municipalities, and public works) to local governments (governorates), to meet local needs, And since the municipality is considered one of the local administrative institutions and most of its goal is to provide increased municipal services to citizens due to population growth and urban expansion of cities by coordinating their actions using their powers, and in order to address gaps in the provision of services, this requires an assessment of the transfer of powers for the purpose of raising the level of coordination between the institutions and relevant departments, To address weakness and develop solutions to develop municipal performance, by presenting concepts of research variables (administrative coordination and municipal performance) in research literature, and using the research approach (comparative), by comparing municipal activities before and after transferring powers to the Directorate of Municipalities of Dhi Qar Governorate as a community and a field of research And with it (19), a municipal institution distributed among the counties and areas of the governorate, for the purpose of identifying the true reality of municipal performance and the extent of the rate of change. Municipal activities in conjunction with the transfer of powers to the governorate, and analysis of the results of the indicators of municipal performance activities, which number (34), an activity for a period of seven years starting from (2013), until the year (2019), after the tasks and actions of the directorate’s people were divided into activities (administrative, legal, Financial, and technical), for the purpose of calculating the percentage of change by employing the statistical measure of the arithmetic mean to learn about the success rate and the effect of coordination in municipal performance, and the most prominent conclusions, the possibility of saying that the experience of transferring powers from the Federal Ministry of Dhi Qar Governorate has the effect of successfully managing the municipalities of the province of Dhi Qar to coordinate and develop performance The municipal, and the most important conclusions, indicate the lack of financial allocations that do not fit with local requirements, as well as the job structure is not suitable for the transfer of powers and may affect coordination of jobs and administrative operations and may lead to weakening the provision of municipal services. Type of research: research paper